An In Vitro Evaluation of Antibacterial Efficacy of Black Pepper Against Periodontal Pathogens - Rashmi S Pattanshetty; Basavaraj S Salagundi; Amit K Walvekar; Jayaprakash S Gadagi (RGUHS Journal of Dental Sciences)
Background Periodontitis is a multifactorial disease primarily resulting from bacterial insult. With the rise in bacterial resistance to antibiotics there is considerable interest in the development of other classes of antimicrobials for the control of infection. Various plant extracts have been used as antibacterial agents and black pepper extract is one such agent.Objective To evaluate the antibacterial potential of black pepper against periodontal pathogens.Methods The ethanolic extract of black pepper was tested against the standard strains of the selected bacteria both gram-positive aerobic and gram-negative anaerobic periodontal pathogens. The parameters assessed were the minimum inhibitory concentration MIC and minimum bactericidal concentration MBC. These tests determined the lowest concentrations of the test agent by evaluating the turbidity for MIC and the presence of few or no bacterial growth colonies for MBC.Results The antibacterial activity at various concentrations against selected microorganisms was shown by the ethanolic extract of black pepper. The mean MIC value of black pepper was reported to be sensitive at 25 mgmL for Porphyromonas gingivalis sensitive at 6.25 mgmL for Aggregatibacter actinomycetemcomitans sensitive at 12.5 mgmL for Actinomyces viscosus and sensitive at 6.25 mgmL for Streptococcus oralis. Black peppers ethanolic extract showed bactericidal activity against P. gingivalis at 25 mgmL concentration. It also showed bacteriostatic activity at all concentrations against A.actinomycetemcomitans A.viscosus and S.oralis.Conclusion This study provides significant insights into the therapeutic effect of black pepper against periodontal pathogens suggesting its potential as an alternative therapy.